2018
DOI: 10.18632/oncotarget.25752
|View full text |Cite
|
Sign up to set email alerts
|

Differential genomics and transcriptomics between tyrosine kinase inhibitor-sensitive and -resistant BCR-ABL-dependent chronic myeloid leukemia

Abstract: Previously, it has been stated that the BCR-ABL fusion-protein is sufficient to induce Chronic Myeloid Leukemia (CML), but additional genomic-changes are required for disease progression. Hence, we profiled control and tyrosine kinase inhibitors (TKI) alone or in combination with other drug-treated CML-samples in different phases, categorized as drug-sensitive and drug-resistant on the basis of BCR-ABL transcripts, the marker of major molecular-response. Molecular-profiling was done using the molecular-inversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Gene expression profiling studies have been performed to identify biomarkers predictive of TKI failure [1416]. In particular, analyses on CML CD34+ cells have revealed that some pathways were consistently deregulated in TKI non-responding patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling studies have been performed to identify biomarkers predictive of TKI failure [1416]. In particular, analyses on CML CD34+ cells have revealed that some pathways were consistently deregulated in TKI non-responding patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that RRM2 may affect the cell survival via the Bcl-2/caspase cell apoptotic pathway and the Akt cell signaling pathway in imatinib therapy. It is noteworthy that different CML phases (chronic phase or accelerated phase) probably affect the level of a certain carcinoma biomarker (39), however, this was not taken into consideration in the present study. Therefore, to gain deeper insight into the predictive value of RRM2 for IR, a larger sample size and a more detailed sample classification are still needed in subsequent investigations.…”
Section: Discussionmentioning
confidence: 88%
“…RNA isolation was done as reported earlier. 12 The Ct value of investigated gene transcripts (SPP1, CDH2, and RIMS2) was measured on 7500 fast Dx Real-Time PCR instruments (Applied Bioscience inc.). Every gene was tested in triplicate for all RNA samples in a single run.…”
Section: Gene Expression Through Quantitative Real-time Pcrmentioning
confidence: 99%